2022
DOI: 10.1007/s11869-022-01237-5
|View full text |Cite
|
Sign up to set email alerts
|

Bushfire smoke plume composition and toxicological assessment from the 2019–2020 Australian Black Summer

Abstract: Many of the population centres in southeast Australia were swathed in bushfire smoke during the 2019–2020 austral summer. Bushfires burning during what is now known as the Black Summer was historically large and severe, and the fire season historically long. The chemical composition in the gas and aerosol phase of aged plumes measured near Wollongong, NSW in early 2020 is reported in this work. Enhancement ratios to carbon monoxide are presented for thirteen species (acetaldehyde, acetone, acetonitrile, black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Overall, oxygenated species comprise nearly 70% of the measured VOCs in wildfire plumes . Elevated formaldehyde and acetaldehyde concentrations have been observed in populated urban areas impacted by wildfire activity, and biomass burning has been described as the predominant source of atmospheric acrolein . Chlorinated hydrocarbons (chloroform and tetrachloroethylene) from wildfires have also been studied and reported in measurements in fire plumes and emissions studies. ,, O’Dell et al reported chloroform and tetrachloroethylene in wildfire smoke plumes in the western US but did not measure carbon tetrachloride.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, oxygenated species comprise nearly 70% of the measured VOCs in wildfire plumes . Elevated formaldehyde and acetaldehyde concentrations have been observed in populated urban areas impacted by wildfire activity, and biomass burning has been described as the predominant source of atmospheric acrolein . Chlorinated hydrocarbons (chloroform and tetrachloroethylene) from wildfires have also been studied and reported in measurements in fire plumes and emissions studies. ,, O’Dell et al reported chloroform and tetrachloroethylene in wildfire smoke plumes in the western US but did not measure carbon tetrachloride.…”
Section: Discussionmentioning
confidence: 99%
“…The later stages of the campaign experienced much less locally-produced smoke. 34 Measurements from the CV-ToF-ACSM were also made at the Kennaook-Cape Grim (KCG) Baseline Air Pollution Station (40.68°S, 144.69°E, Fig. 1b) between February 2021 and September 2022 as part of the ongoing long term monitoring program at KCG.…”
Section: Sampling Locationsmentioning
confidence: 99%
“…Extreme pollution events can also occur in warmer months due to wildfires (e.g. Rea et al 2016;Simmons et al 2022). Owing to heterogeneity in the frequency, magnitude and characteristics of poor air quality events throughout the year, it is useful to examine atmospheric pollutant concentrations through a seasonal lens.…”
Section: Introductionmentioning
confidence: 99%